Rigorous modeling of the Traveling Grate stage in the iron ore pellet induration process - C.B. Cavalcanti; G.F.N. Wanderley; D. Braga; R.P. Brito; L.G.S. Vasconcelos; K.D. Brito (Journal of Materials Research and Technology, 2024)
This work presents a robust phenomenological model for the Traveling Grate system in an iron ore pellet induration plant on an industrial scale. The system consists of a bed of pellets in constant movement, heated by perpendicular air currents. The aim is to integrate into a single model the details of the chemical and physical phenomena that occur in the system, including gas/pellet energy transfer, a three-stage drying mechanism, compressive strength, and kinetic models for coke combustion, magnetite oxidation, and carbonate calcination. The model demonstrated adherence to process data, with a maximum relative deviation of 2.35%. Simulations enabled the assessment of the influence of key parameters on the bed temperature, observing an inversely proportional relationship of the profile for grate velocity, pellet diameter, and bed height. Pellet quality was analyzed under different composition conditions and void fractions, highlighting the significant influence of the coke on compressive strength, limited by the vitrification phenomenon at high temperatures. This model enables critical analysis of phenomena that are difficult to detect in conventional operations and helps in defining operational ranges to optimize product quality and process energy efficiency.